PELATIHAN PEMBELAJARAN DARING MEGGUNAKAN MEDIA PEMBELAJARAN AUDIO -VISUAL UNTUK GURU-GURU DI SMA N I TANAH MIRING - Mitra Rahayu; Dessy Rizki Suryani; Jeffri Parrangan (Musamus University, 2021)
In implementing the teaching and learning process the teacher must use learning media that is attractive, innovative and in accordance with the material being taught. Learning media made by teachers must also develop, especially to keep pace with technological developments. As well as in the development of technology teachers must also be able to DARING learning, especially in circumstances that do not allow face-to-face learning, for example, such as during the current Covid-19 pandemic. The problem faced by teachers at SMA N I Tanah Miring is that many teachers still encounter problems in making technology-based learning media and conducting online learning. So that in the implementation of this service, there will be training for teachers at SMA N I Tanah Miring in making audio-visual learning media (voice ppt and learning videos), as well as creating and implementing DARING learning using google classroom. Learning media in the form of voice ppt and learning videos that have been made previously will be included in the google classroom so that it can make it easier for teachers in delivering lesson material. The method in implementing this service includes stage I (observation / survey) the obstacles faced by the teacher in conducting learning at this time, stage II (training / socialization) implementation of training activities to make audio-visual media and conducting DARING learning, stage III (Evaluation) after being carried out training then an evaluation will be carried out to see the success of the training and the sustainability of the training being carried out